Design science research methods and patterns innovating information and communication technology - Vaishnavi, Vijay; Kuechler, William (Auerbach Publications, 2015)
This edition describes a simple and practical methodology for conducting cutting-edge design science research (DSR). It provides guidance on how to conduct such research and supplies in-depth treatment of design science theory and the different types of theory that can be generated in design science research. Making novel use of the concept of patterns, it presents 84 research patterns for conducting DSR. It emphasizes design science theory and is filled with examples of using patterns to conduct information and communication technology research (ICT) and relies on familiar patterns to provide the fundamentals of various research philosophies and techniques required to innovate ICT. New topics include: design science research patterns adapted from TRIZ; expanded treatment of theory building in design science research (DSR); examination of patterns in DSR presented using a new pattern classification mechanism to group patterns with like functionality